Inland Fisheries Production Condition with Production Unit-Wise Productivity and Production Growth Rate in Bangladesh - Mehedi Hasan Manik (Jurnal Multidisiplin Madani, 2023)
In Bangladesh, 85% of fisheries yield comes from inland fisheries. There is an evident production gap between the inland capture and culture fisheries in sample data, but what is in population? The study evaluates the production gap between inland capture and culture fisheries by appropriate test statistics and traces the production share, productivity, yield area, and growth status of various production units of inland fisheries. The required data have been collected from the website of the department of fisheries of Bangladesh. To evaluate the production gap, the study relies on the Mann-Whitney-Wilcoxon U test. The P-value, 0.02272 < 0.05, suggested that there is a significant yield gap between the population of inland capture and culture fisheries in Bangladesh. Inland capture and culture controlled 82.06% and 17.94% of inland production area and 33.03% and 66.97% of production, respectively. The productivity of the inland culture fishery is 9.2 times higher than the inland capture. Rivers, floodplains, and ponds combinedly control 83.07% of the inland production area and 82.57% of the inland yield. To achieve the vision of Bangladesh, policymakers should make separate fishery policies for rivers, floodplains, and ponds. This study might be helpful to national and international bodies to understand the inland fisheries population and production units which might be helpful to restructure fisheries policy in Bangladesh